Analysis of a Uniform Linear Broadside Dipole Antenna Array Operating at 1.8 GHz for Use in GSM Application. - Mahmood, Aras Saeed; Ibrahim, Dlnya Aziz (Sulaimani Journal for Pure and Applied Sciences, 2016)
A uniform broadside array antenna is the arrangement of equally spaced and equal current amplitude excitation of identical antennas, which are placed along the axis perpendicular to the direction of maximum radiation. The overall radiation pattern of an array is determined by array factor combined with the radiation pattern of the antenna element. The number of the elements and their spacing may produce the diverse radiation properties. In this work the impact of these two factors on the radiation characteristics of a uniform linear broadside dipole array were analyzed using the 4NEC2 simulation software. The spacing between the elements varied from 0.1λ to 2λ in steps of 0.02λ for a number of elements up to 10 elements. For GSM application at 1.8GHz frequency the best configuration to achieve the required gain of 13.8dBi was 7-elements with 0.88λ spacing
Keywords: GainHalf power beamwidthRadiation patternMax Side lobe levelNo of side lobes